Iceberg melting substantially modifies oceanic heat flux towards a major Greenlandic tidewater glacier - Davidson, B. J.; Cowton, T. R.; Cottier, Finlo Robert; Sole, A. J. (Nature Communications, 2020)
Fjord dynamics influence oceanic heat flux to the Greenland ice sheet. Submarine iceberg melting releases large volumes of freshwater within Greenland’s fjords, yet its impact on fjord dynamics remains unclear. We modify an ocean model to simulate submarine iceberg melting in Sermilik Fjord, east Greenland. Here we find that submarine iceberg melting cools and freshens the fjord by up to ~5 °C and 0.7 psu in the upper 100-200 m. The release of freshwater from icebergs drives an overturning circulation, resulting in a ~10% increase in net up-fjord heat flux. In addition, we find that submarine iceberg melting accounts for over 95% of heat used for ice melt in Sermilik Fjord. Our results highlight the substantial impact that icebergs have on the dynamics of a major Greenlandic fjord, demonstrating the importance of including related processes in studies that seek to quantify interactions between the ice sheet and the ocean.